Distribution pattern and titer of Candidatus Liberibacter asiaticus in periwinkle (Catharanthus roseus) - Ya LI; Mei-rong XU; Ze-han DAI; Xiao-ling DENG (Journal of Integrative Agriculture, 2018)
Candidatus Liberibacter asiaticus (CaLas), an uncultured Gram-negative alphaproteobacterium, is the causal agent of Huanglongbing (HLB) in citrus. CaLas resides in phloem sieve tubes and has been shown to be unequally distributed in different tissues. Although HLB is a disease of citrus plants, it has been demonstrated that periwinkle can serve as an experimental host of CaLas, which can be transmitted from citrus to periwinkle via the parasitic plant dodder (Cuscuta spp.). To investigate the distribution of CaLas in various periwinkle tissues, the bacteria were transmitted from an infected periwinkle plant to healthy periwinkles by top-grafting. The movement of the inoculum and associated titer changes were observed over time in various tissues. CaLas could be detected in the leaves, main stems, and roots of infected periwinkle by conventional PCR, and in all three tissues a clear time-dependent change in CaLas titer was observed, with titer increasing soon after inoculation and then decreasing as disease symptoms became severe. The highest titer was found at 25, 35 and 35 days after inoculation in leaves, main stems and roots, respectively. The titer in leaves was much higher than in the main stems and roots at the same time point, and the spatial distribution of CaLas in the leaves, main stems and roots of infected periwinkle was uneven, similar to what has been shown in citrus. The results provide guidance for selecting the proper periwinkle tissues and sampling times for early detection of CaLas.